2004
DOI: 10.1017/s1355770x03001098
|View full text |Cite
|
Sign up to set email alerts
|

Valuing health damages from water pollution in urban Delhi, India: a health production function approach

Abstract: Diarrhoeal diseases are endemic in Delhi. The causes of diarrhoeal illness involve both the household and the public sector as a provider of a public good, namely water supplies. Questions of both adequacy and quality of the water supply available to the household for drinking purposes are of crucial importance. The present study conducts an objective assessment of the health damages incurred by urban households by adopting a health production function approach. A model for valuing the damages from contaminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…McConnell and Rosado (2000) use the data from Brazil and find that the demand for home purification is positively affected by factors such as income, education and presence of young children in the household. Income and education are also some of the variables that positively affect the demand for home purification in the study of Dasgupta (2004). Among the factors affecting the choice of a specific purification method, McConnell and Rosado (2000) found that the more and alternative costs, the less likely it will be choose.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…McConnell and Rosado (2000) use the data from Brazil and find that the demand for home purification is positively affected by factors such as income, education and presence of young children in the household. Income and education are also some of the variables that positively affect the demand for home purification in the study of Dasgupta (2004). Among the factors affecting the choice of a specific purification method, McConnell and Rosado (2000) found that the more and alternative costs, the less likely it will be choose.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is not surprising, since more educated households are probably more aware about adverse health effects from ingestion of poor water quality. Several other studies put in evidence the impact of education on the decision to purify water (McConnell and Rosado, 2000;Dasgupta, 2004;Nauges and Van Den Berg, 2009, etc.). The study also suggests that education increases the probability of adopting an improved water source.…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 99%
“…Broadly speaking, climate change causes 150 000 excess deaths annually while indoor pollution kills 2 millions people in 2012. This phenomena has often been addressed by economists and is also a major concern for many physicians (see among others Pope (2000), Chay and Greenstone (2003), Dasgupta (2004), Evans and Smith (2005), WHO (2004WHO ( , 2006). Most empirical studies usually conclude to a significant and detrimental impact of air (or/and water) pollution on health status, in particular those of children and elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no systematic study has been performed to assess the economic impacts of wastewater use in crop production in Ethiopia prior to this study. While empirical studies have attempted to measure the health costs of air pollution (Gerking and Stanley, 1986;Alberini, 1997) as well as drinking water supply and sanitation (Harrington et al, 1989;Dasgupta, 2004), this study differs from the other studies mainly because it focuses on the health cost of wastewater reuse for crop production. wastes into surface water bodies by a large margin, especially the values for biochemical oxygen demand (BOD), phosphate, suspended solids (SS), ammonia (NH 3 ) and total coli form bacteria (Environmental Protection Authority, 2003).…”
Section: Description Of the Study Areamentioning
confidence: 99%